“Speak now or forever hold your peace”: The gendered constructions of extra-marital affairs found in South African online media. - Muncina, Buyisile Nomfundo (My University, 2017)
The purpose of the study was to speak to the dynamics involved in the construction of extramarital affairs in South African news media. At the core of the study was the need to understand and deconstruct the discourses that trail behind the emergence and chaos that follows a publicised marital affair. In this process, the investigation was based on the critical analysis of newspaper articles and their portrayal of the man, the wife and the mistress in light of an extra-marital affair. The design of the study was qualitative and used thematic discourse analysis to comb through the narratives and the style of reporting so as to draw out what was both said and left unsaid concerning the marital affair. Major findings in this study showed an unchanged perception of the mistress and the wife as history carries the mistress as an object for the pleasure of the man, whilst the wife is to ensure that the dignity and purity of her marriage remains untainted. Additionally, the study also showed the pardon of men and the rendering of their masculinity as fragile. The affair is seemingly a result of a seductress who uses her sexual prowess to lure a sexually vulnerable man. From this, it can be concluded that men hold sexual privilege over women and indeed in the reporting of the affair, it takes a gendered tone in favour of the man- normalising their response and reactions, whilst crucifying the mistress for contributing to the disintegration of the marriage. The wife gains sympathy from the social audience which gives her a renewed strength to fight for her marriage.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Community-Based Counselling Psychology, June 2017
Keywords: Adultery--South Africa--Psychological aspects; Man-woman relationships--South Africa; Press--South Africa